Optimizing SQL Injection Prevention: A Multi-Layered Defense Approach - Lokesh Kumar,; Dr. Pramesh Srivastava, (International Journal of Scientific Research in Science and Technology, 2025)
SQL injection (SQL) remains one of the most critical threats to database security, leading to unauthorized data access, manipulation, and breaches. This paper explores advanced optimization techniques for SQL injection prevention by integrating prepared statements, rigorous input validation, and Web Application Firewalls (WAFs). The study evaluates the effectiveness of parameterized queries, whitelist validation, and AI-driven real-time monitoring in mitigating risks. Through empirical analysis and case studies, we demonstrate how a multi-layered defense strategy significantly reduces vulnerabilities while maintaining performance efficiency. The findings provide actionable insights for developers and organizations to enhance cyber security frameworks against evolving SQL threats.
Keywords: SQL Injection Prevention; Cyber security; Mitigation Secure; Coding Practices; SQL Protection Mechanisms